Associations between vitamin D, adiposity, and respiratory symptoms in chronic spinal cord injury. (2nd November 2018) - Walia, Palak; Goldstein, Rebekah L.; Teylan, Merilee; Lazzari, Antonio A.; Hart, Jaime E.; Tun, Carlos G.; Garshick, Eric
Context/Objective: Persons with chronic spinal cord injury (SCI) have an increased risk of respiratory-related morbidity and mortality and chronic respiratory symptoms are clinical markers of future respiratory disease. Therefore, we sought to assess potentially modifiable factors associated with respiratory symptoms, with a focus on circulating vitamin D and measures of body fat. Design: Cross-sectional study. Setting: Veterans Affairs Medical Center. Participants: Three hundred forty-three participants (282 men and 61 women) with chronic SCI participating in an epidemiologic study to assess factors influencing respiratory health recruited from VA Boston and the community. Methods: Participants provided a blood sample, completed a respiratory health questionnaire, and underwent dual x-ray absorptiometry (DXA) to assess % body fat. Logistic regression was used to assess cross-sectional associations between respiratory symptoms and plasma vitamin D and measures of body fat with adjustment for a number of potential confounders. Outcome Measures: Chronic cough, chronic phlegm, any wheeze, persistent wheeze. Results: After adjustment for a number of confounders (including smoking), participants with greater %-android, gynoid, trunk, or total body fat had increased odds ratios for any wheeze and suggestive associations with persistent wheeze, but not with chronic cough or phlegm. Vitamin D levels were not associated with any of the respiratory symptoms. Conclusion: Increased body fat, but not vitamin D, was associated with wheeze in chronic SCI independent of a number of covariates.